Potential of stem cell therapy during dengue infection in mice - Maideensa Syed Gulam, Sakinah (2017)
Dengue is one of the most common arthropod-borne infections in the world which has been the major concern to the governments and World Health Organization (WHO). The virus causes over 390 million infections annually. Individual infected with dengue virus are suffering from several clinical symptoms including leukopenia, thrombocytopenia and hemorrhagic manifestations. Stem cell based therapy has been widely used for many disorders. The advance in regenerative therapy promises the alternative therapy for infectious diseases. Researchers reported about the stem cells treatment for infections in relation to HIV, malaria and tuberculosis. The success of these reports had laid a positive path to work in current objective, to investigate the potential of stem cells and progenitor cells with the growth factor infusion in protecting and repairing the injuries in dengue infected mice. Eight week old male BALB/c mice were divided into three groups; Control group: mice injected with eagle minimum essential media (EMEM) and phosphate buffer saline (PBS); Group 1: mice infected with DV-2 (G1); Group 2: mice infected with DV-2 and treated with hematopoietic stem cells (HSCs), endothelial progenitor cells (EPCs) and growth factor (GF) (G2). Mice in G1 and G2 were inoculated with DV-2. At day 2 of post infection, mice in G2 were infused stem cells (HSCs, EPCs and GF) intraveneously. Blood was collected from all groups at 5th, 10th, 15th, and 21st d.p.i for hematological assay, biochemical assay, and sacrificed for histopathological analysis and viral clearance analysis. Dengue infection in G1 results in thrombocytopenia, leucopenia and lymphocytopenia by 21st d.p.i, with low hemoglobin level and red blood cells count. Additionally, the biochemical assays (AST & ALT) increased showing significant correlation with the histopathological damages in liver. Moreover, blood vessel histopathology revealed injury correlating to the blood profile and all the damages was persistent till 21st d.p.i. The DV-2 infection with stem cell treatment group (G2) exhibits protective effect in blood profile, liver, blood vessel histopathology and viral clearance with the recovery initiated from 10th d.p.i. In conclusion, stem cell could be a new potential therapy not only to recover the altered blood profile, severe organ structural injury with its protective effect, but also completely clear the viral particle in order to help in normal body functioning.